Intercultural Communication in Manuscript Digitization (Study in the Village of Legok Indramayu) - Tantry Widiyanarti; Sarwititi Sarwoprasodjo; Ahmad Sihabudin; Rilus A. Kinseng (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2021)
Manuscript digitization is an effort to preserve the content of the manuscript from damage. The content of the manuscript which contain local wisdom must be saved, because the manuscript is old and is in a concerning condition, damaged, destroyed, or even lost. Therefore, digitalization needs to be done. However, digitalization cannot be done easily, because there are cultural differences that underlie it. This study wants to see how intercultural communication is carried out during the process of digitizing a manuscript so that digitization can be carried out. This study uses a qualitative method with observation, interview, and data triangulation techniques. This research is useful to add insight and make it easier for the digitizer to digitize the manuscript if he meets a manuscript owner with a different culture than the digitizer. The result or finding is that the intercultural communication used in digitizing manuscripts uses a cultural dimension approach so that digitization can be carried out.Keywords: Manuscript digitization, power distance, uncertainty avoidance, the collectivism-short term communication ABSTRAKDigitalisasi naskah ialah upaya untuk melestarikan isi naskah dari kerusakan. Isi naskah yang berisi local wisdom harus diselamatkan,karena usia naskah sudah tua dengan kondisi yang prihatin, rusak, hancur, bahkan hilang. Karena itu digitalisasi perlu dilakukan. Namun, digitalisasi tidak dapat dilakukan dengan mudah, disebabkan ada perbedaan budaya yang mendasarinya. Penelitian ini ingin melihat bagaimana komunikasi antarbudaya yang dilakukan ketika proses digitalisasi naskah sehingga digitalisasi dapat dilakukan. Penelitian ini menggunakan metode kualitatif dengan teknik observasi, wawancara dan triangulasi data. Penelitian ini berguna menambah wawasan dan memudahkan pendigital dalam melakukan digitalisasi naskah, jika bertemu dengan pemilik naskah yang berbeda budayanya dengan pendigital. Hasil atau temuan penelitian ini adalah komunikasi antarbudaya yang digunakan dalam digitalisasi naskah menggunakan pendekatan dimensi budaya sehingga digitalisasi dapat terlaksana. Kata Kunci: Digitalisasi naskah, power distance, uncertainty avoidance, collectivism-short term orientation, low level communication